China Capital Markets Development Report : China Securities Regulation Commission - Qi, Bin (China Financial Publishing House, 2013)
The 'China capital markets development report' provides a good overview of the development of China's capital markets and explores future strategies. The report starts by reviewing historical events in the evolution of China's capital markets which have grown from small and unorganized regional markets into a national market today. By summarizing lessons learned during the market evolution and analyzing major gaps between China's capital markets and more mature markets, the report tries to propose a strategic design and vision for China's capital markets development for the next decade and beyond. Since the commencement of economic reform and opening up, China has gone through significant economic and social changes, and the socialist market economic regime has been established and steadily improved. Between 1979 and 2007, China's Gross Domestic Product (GDP) has been growing above 9 percent annually on average and China has become the fourth largest economy in the World. China's capital markets emerged and developed during the same period. With joint efforts by all relevant parties, China's capital markets have been able to reach a level of development that took many mature markets decades or even a hundred years to achieve. Along the way, the legal and regulatory frameworks, and trading and clearing systems have developed according to international best practice and China's capital markets have been increasingly recognized by international investors. The emergence and development of capital markets has been closely linked to mass production. They are the prerequisite for, and important indicators of, a modern market economy. Capital markets promote the development and improvement of market-driven resource allocation, resulting in the optimization of social resources. As the world financial markets become increasingly global and integrated, competition among capital markets and financial centers around the world is becoming increasingly intensive, leading to a fast-changing landscape in capital markets. The competitiveness and viability of the capital markets have become important components of national competitiveness.